Dissent from Mt. Ventoux: Between Christian and Secular Humanism in Petrarch’s de Ascensu Montis Ventosi - Ellis, Erik Z. D. (Scripta Mediaevalia, 2021)
Petrarch’s letter de Ascensu Montis Ventosi has long served as the founding document of “renaissance humanism”. Since the beginning of renaissance studies in the mid-nineteenth century, the letter has become almost a talisman for summoning the new, secular spirit of humanism that spontaneously arrived in Italy in the fourteenth century, took hold of the hearts and minds of Europeans in the fifteenth century, and led to cataclysmic cultural, religious, and political changes in the sixteenth, seventeenth, and eighteenth centuries. This reading, still common among non-specialists, especially in the English-speaking world, is overly simplistic and ignores Petrarch’s profound debt to classical and Christian tradition, obscuring the fundamentally religious character of the letter. This article examines how scholars came to assign the letter so much importance and offers an interpretation that stresses Petrarch’s continuity with tradition and his desire to revitalize rather than reinvent the traditions of Christian scholarship and contemplation.